2023
DOI: 10.1177/14673584231173508
|View full text |Cite
|
Sign up to set email alerts
|

Female solo travels to south Asian destinations and sustaining loneliness

Abstract: While there has been an increase in the number of tourists travelling solo, there is a steady growth in females travelling alone as tourists around the globe. This phenomenon has led to a growing scholarly interest, yet solo female travel as a research topic is relatively under-researched. Only limited knowledge exists about the psychological issues of female solo travel, such as loneliness. There is a gap in our understanding of interpreting solo travel by females, depending on their country of origin and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Unlike family or group travellers, who primarily interact with their companions, solo female travellers often engage with fellow guests, roommates, or the host in shared accommodations. This interaction aligns with existing studies on motivations, such as social interaction factors [12], the opportunity for connectedness with people [43], or the challenge of loneliness [44]. It is also a cost-saving or risk-mitigating strategy, emphasizing the importance of the social aspect of their lodging experience.…”
Section: Identifying Satisfiers and Dissatisfiers In Traditional And ...supporting
confidence: 78%
See 2 more Smart Citations
“…Unlike family or group travellers, who primarily interact with their companions, solo female travellers often engage with fellow guests, roommates, or the host in shared accommodations. This interaction aligns with existing studies on motivations, such as social interaction factors [12], the opportunity for connectedness with people [43], or the challenge of loneliness [44]. It is also a cost-saving or risk-mitigating strategy, emphasizing the importance of the social aspect of their lodging experience.…”
Section: Identifying Satisfiers and Dissatisfiers In Traditional And ...supporting
confidence: 78%
“…Osman et al's [12] study on Vietnamese solo female travellers concluded with two categories of motivations: personal factors, including freedom and flexibility, self-empowerment, independence, and exploration; social interaction factors, such as lack of companions and the opportunity to meet new people. More specifically, they are inspired by the opportunity to seek freedom, self-development and self-enhancement, being autonomous through travelling solo, and connectedness with people [1,12,43]. Similarly, Breda et al's [44] study, which focused on Portuguese women, identified the key motivations of solo female travellers as including the absence of a travel companion, freedom of choice, the pursuit of adventure and experience, and escaping from the daily routine.…”
Section: Solo Female Travellersmentioning
confidence: 99%
See 1 more Smart Citation
“…The main studied topic on SFTs is travel experiences, which refer to the evaluations that occur after the trip (Woodside and King, 2001) (also see Box 3 in the TPCS model) (Neluhena et al , 2023; Yang et al , 2019; Nikjoo et al , 2021; Su and Wu, 2020). Travel experience tends to be evaluated holistically rather than on a single attribute (Chen and Chen, 2010) and can be pleasant or unpleasant feelings about their trip.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews of the travel experiences of these SFTs revealed different travel experiences from the non-SFTs. SFTs’ travel experiences improve intrapersonal development, including freedom pursuit, being with self, self-enhancement and confidence (Neluhena et al , 2023; Jordan and Gibson, 2005), meaning-making, power and empowerment and facilitation of self-awareness and transformation (Nikjoo et al , 2021). Non-SFTs’ travel experiences improve one's relationships and bond with others who travel together, such as family and friends (Durko and Petrick, 2013; Heimtun and Abelsen, 2012).…”
Section: Resultsmentioning
confidence: 99%